The impact of venture capital financing on the long-term performance of startups: a managerial perspective - Vadim Limar (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
In this article the authors explore the effect of venture capital financing on long term performance of startups in the European Union by looking at the influence of managerial experience, efficiency of resource allocation and strategic usage of venture capital investment. The research using a panel data analysis of 10 startups from the period from 2019 to 2023, evaluates the influence of venture capital on startups growth trajectories and operational success. Results suggest that startups run by management teams with prior experience utilizing venture capital are more likely to leverage funds wisely compared to startups whose management teams do not have prior experience with venture capital. Moreover, resource allocation becomes efficient, especially towards research and development, marketing, and scaling operations to achieve superior longer run performance outcomes. The challenge of fund raising is also underlined, as the importance of strong relationships with the venture capital investors, that are not just sources of capital but can also provide strategic guidance and networks. The research also analyzes some issues companies struggle with, such as competition, volatile markets, and managing the complexity of scaling operations.